Innovations in consumer research: The virtual food buffet. (January 2018) - Ung, Chin-Yih; Menozzi, Marino; Hartmann, Christina; Siegrist, Michael
Highlights: Proof of concept that the virtual food buffet is a useful tool. Virtual reality is a promising method for human nutritional behavior research. Participants behaved similar in the virtual reality and in the fake food condition. Abstract: Experimental studies are important in the process of gaining a better understanding of people's food choices. The present study, which tested the validity of a virtual food buffet, delivers a proof of concept. The proposed method uses virtual reality to simulate a buffet with three different foods from which participants could serve a meal. To determine the validity of the new method, a fake food buffet—known to be a valid and reliable method—was used as a comparison. A sample of 34 participants served themselves two meals, one in virtual reality and one from a fake food buffet. The order of the two buffets was randomized. We observed high correlations between the kJs of the foods served in the two conditions ( r  ≥ 0.75, p  < 0.001). Our results suggest that the virtual food buffet is a useful research method. Virtual reality seems to be a promising method for examining the impact of environmental cues on human nutritional behavior.